MATERNAL MORTALITY IN PAKISTAN: IS THERE ANY METAMORPHOSIS TOWARDS BETTERMENT? - Nisar, Nusrat; Abbasi, Razia Mustafa; Chana, Shehla Raza; Rizwan, Noushaba; Badar, Razia (Journal of Ayub Medical College Abbottabad, 2017)
Background: Every year more than half million mother die due to pregnancy related preventable causes like haemorrhage, hypertensive disorders, sepsis, obstructed labour and unsafe abortion. Among these deaths 99% occur in developing countries. The study was conducted to assess the maternal death rate and to analyse its trends over a period of 20 years in tertiary care hospital in Sindh Province Pakistan. Methods: A retrospective analysis of maternal mortality records were carried out for a period of 20 years from 1986-1995 and 2011-2015 at the Department of Obstetrics and gynaecology Liaquat University of Medical and Health Sciences Hyderabad Sindh Pakistan. The record retrieved was categorized into four 5 yearly periods 1986-1990, 1991-995, 2006-2010 and 2011-2015 for comparison of trends. Results: The cumulative maternal mortality ratio (MMR) was 1521.5 per 100,000 live births. The comparison of first 5 years' period (1986-1990) and last 5 years (2011-2015) showed downward trend in maternal mortality rate from 2368.6-1265.1. Direct causes of death have accounted for 2820 (84.78%) of total maternal death. Sepsis was the major cause of death for first 5 years accounted for 196(35.1%) of maternal death while in the last 5 years' eclampsia causes 284 (27.84%) of direct maternal deaths. Conclusion: The reduction in the maternal deaths has been very slow. The direct causes were still the main reasons for obstetrical deaths. Keywords: Maternal Mortality; Changing trends; Women's Health; Safe Motherhood